A study on the impact of artificial lighting on insect diversity in China's urban ecotone: a case study of Tianjin. Issue 1 (September 2021) - Yu, Z; Liu, G.
Abstract: This paper analyses the experiments conducted in Tianjin, an important ecological interlocking area in North China, and can basically draw the following conclusions. (1) Tianjin's urban ecological interlocking area is rich in insect species, has good stability, and is more affected by artificial lighting. (2) The attraction of artificial lighting lights to insects has a certain relationship with the spectrum and space, which has a lot to do with the wavelength composition of artificial lighting lights. Although the wavelength increases, the attraction decreases. (3) The attractiveness of white light lamps with a colour temperature of 4500k to insects is greater than that of white light lamps with a colour temperature of 3000k.